New allelic variant of autosomal recessive hereditary motor and sensory neuropathy type 2S resulted from mutations in gene IGHMBP2 - E. L. Dadali; I. V. Sharkova; S. S. Nikitin; F. A. Konovalov (Нервно-мышечные болезни, 2016)
Hereditary motor and sensory neuropathy (HMSN, Charcot–Marie–Tooth disease) is a group of genetically heterogeneous disorders with more than 80 genes linked to different phenotypes, including IGHMBP2 gene responsible for HMSN type 2S (OMIM 616155). Until recently, mutations in IGHMBP2 were exclusively associated with neonatal distal spinal muscular atrophy with respiratory distress (SMARD1, OMIM 604320). A case report presents a boy with infant onset decreased distal muscle tone and weakness, distal wasting and deformation in legs and hands, areflexia and decreased sensation without respiratory involvement; at age seven he had severe fixed kypho-scoliosis. EMG revealed signs distal axonal neuropathy. The exsome sequencing confirmed the allelic variant of two compound heterozygous mutations in gene IGHMBP2: known missens mutation с.1616С>Т (р.Ser539Leu) in exone 11 and a novel deletion с.2601_2602delGA in exone 13. The diagnosis of infant HMSN type 2S was confirmed. The phenotype of HMSN type 2S and its diagnostics differences between SMARD1 are discussed.